2019
DOI: 10.4238/gmr18182
|View full text |Cite
|
Sign up to set email alerts
|

Research Article Line selection and correlation between traits of soybean genotypes under high naturally occurring stink bug infestation

Abstract: The soybean crop is undoubtedly important to not only Brazil but also for most parts of the globe, as economic and social dependency upon this crop becomes evident. However, the scenario of the soybean crop production has faced challenges with environmental changes, which have escalated the incidence of pests. Due to the abundance of stink bugs, especially Euschistus heros in tropical regions, they can considerably impact the productivity of the crop compromising total grain yield and seed quality. Therefore, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…This is different from the study by Xu et al [29] who reported that the number of pods per plant increased when the number of branches increased, while the pod number per unit area decreased. In other studies, it was also reported that there was a phenotypic correlation between plant height and the number of nodes on main stem [30] and HGT and POF [7].…”
Section: Resultsmentioning
confidence: 99%
“…This is different from the study by Xu et al [29] who reported that the number of pods per plant increased when the number of branches increased, while the pod number per unit area decreased. In other studies, it was also reported that there was a phenotypic correlation between plant height and the number of nodes on main stem [30] and HGT and POF [7].…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, we cannot infer that metabolite variability can be a direct consequence of transgene insertion. We also have UFUS Xavante, a conventional cultivar obtained through genetic improvement in this grouping (Jorge et al, 2019).…”
Section: Influence Of Chemical Profile On the Resistance Of Glycine M...mentioning
confidence: 99%